Resposta do bicarbonato de sódio e da glicemia no exercício de agachamento - Moreira, Leonardo Ítalo Costa (2016)
Introduction: Glycemia is the amount of sugar found in the blood, which comes from the breakdown of carbohydrates called glycolysis, this glycemia can increase due to the demand of the exercise in order that the musculature currently worked has a source of energy for it to be performed the movement. Objective: To verify glycemia with the use of sodium bicarbonate supplementation BCS in squatting exercise with free bar. Material and Methods: Fifteen volunteers performed 6 sets of squats, where they performed a sodium bicarbonate supplementation 1 hour before the test, the blood glucose was analyzed in three moments, Pretest, Posttest and 30 minutes after the end of the test. Results: There was no difference between BCS and PLA at the pre-time (p = 0.153) and at the post-time (p = 0.274). However, at the 30min point, glycemic concentration was significantly higher in placebo (p = 0.011). There was no significant difference between the Pre, Post and 30 min moments in BCS and PLA (p> 0.05). Conclusions: The present study found that glycemia did not change with the use of sodium bicarbonate.